2017
DOI: 10.1371/journal.pone.0187241
|View full text |Cite
|
Sign up to set email alerts
|

Associations between thyroid dysfunction and developmental status in children with excessive iodine status

Abstract: Background and objectiveAdequate iodine status and normal thyroid hormone synthesis are important for optimal child development. In this study, we explored whether young children’s developmental status is associated with thyroid dysfunction in an area of chronic excessive iodine exposure.MethodsWe included 298 children between 18 and 48 months of age residing in Algerian refugee camps. Early child development was measured using the Ages and Stages Questionnaires, third edition (ASQ-3), consisting of five domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 54 publications
2
20
0
Order By: Relevance
“…Although infants may be particularly vulnerable to excessive iodine intake (7,65,71), no thyroid dysfunction was observed in this study, suggesting that the infant thyroid may adapt to high iodine intake when chronic. However, the longterm consequences of thyroidal stress during infancy are uncertain, and the results conflict with findings elsewhere (10,72,73). Long-term follow-up of infants exposed to excessive iodine intake for long periods is required.…”
Section: Excess Iodine Intake Increases Tg Concentrations 1205mentioning
confidence: 94%
“…Although infants may be particularly vulnerable to excessive iodine intake (7,65,71), no thyroid dysfunction was observed in this study, suggesting that the infant thyroid may adapt to high iodine intake when chronic. However, the longterm consequences of thyroidal stress during infancy are uncertain, and the results conflict with findings elsewhere (10,72,73). Long-term follow-up of infants exposed to excessive iodine intake for long periods is required.…”
Section: Excess Iodine Intake Increases Tg Concentrations 1205mentioning
confidence: 94%
“…Thyroid hormones, thyroxin (T 4 ) and triiodothyronine (T 3 ), are essential for the synthesis of growth hormones, cell differentiation, and metabolism, and they are crucial for the growth and development (1) . Both iodine deficiency and iodine excess are known to interfere with thyroid hormone synthesis (2,3) .…”
Section: Introductionmentioning
confidence: 99%
“…High iodine concentration in urine among women and children has previously been examined and published [ 21 , 23 , 39 ]. These studies found a high prevalence of biochemically assessed thyroid dysfunction among both women and children, which might have been caused by excessive iodine intakes.…”
Section: Discussionmentioning
confidence: 99%